2018
DOI: 10.1002/xrs.2987
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the demineralization induced in human enamel by an acidic beverage using X‐ray fluorescence spectroscopy and Raman microscopy

Abstract: This study was conducted with the purpose of evaluating the demineralization effect of a widely consumed acidic soft drink, Coca-Cola®, in human enamel. This way, an in vitro model for the daily intake of this beverage was developed taking into account the intraoral environment. The evaluation of the enamel specimens was undertaken considering two approaches, the direct analysis of enamel surface and the study of specimens as cross sections. The depolarization ratio of the phosphate symmetric stretching band i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Candido et al and Ko et al, using Raman spectroscopy, showed that the arrangement of apatite crystals is altered in demineralized enamel, since they present a more disordered structure. Accordingly, in demineralized enamel, the depolarization ratio value is higher [ 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candido et al and Ko et al, using Raman spectroscopy, showed that the arrangement of apatite crystals is altered in demineralized enamel, since they present a more disordered structure. Accordingly, in demineralized enamel, the depolarization ratio value is higher [ 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy has been used to evaluate the symmetric stretching mode of the tetrahedral phosphate group (PO43-, with a Raman shift of ~959 cm −1 ) and infer upon the mineral phase of enamel [ 18 ]. Fraser et al evaluated changes in the intensity and peak shape of this Raman band, together with the ratios to the amide I and carbonate, to study teeth affected with MIH [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in precision is further highlighted by the determination of the depolarization ratio (ρ959), revealing lower uncertainties when using the 785 nm laser (Table 1). The depolarization ratio is indicative of the soundness of teeth [12], presenting increased values for demineralized enamel [23,24]. Although the results obtained with both lasers are in agreement, samples S2 and S6 present higher depolarization ratio, while samples 3, 4 and 5 are more difficult to differentiate; the higher uncertainties rendered by measurements with the red laser would not allow to distinguish between sound and demineralized enamel with the main purpose of performing such an analysis.…”
Section: Evaluation Of the Suitability Of Laser Wavelength For Enamel...mentioning
confidence: 85%
“…For each sample, an average of 20 measurements (10 different points with parallel polarization, always followed by other 10 with orthogonal polarization) were performed, with an exposure time for each measurement of 20 s with 4 accumulations. The following parameters were obtained and compared in each step of the study: depolarization ratio (ρ959), anisotropy, Raman shift wavenumber and full width at half maximum (FWHM) of the symmetric stretching band of phosphate (~959 cm −1 ), according to Pessanha et al [24].…”
Section: Methodsmentioning
confidence: 99%
“…[12,13] Raman analysis makes it possible to determine caries lesions that occur as a result of demineralization and the changes in molecules, such as Ca and PO 4 À3 , during the processes of treating these lesions with remineralization agents. [14][15][16][17] In the literature review, no study was found to assess the molecular changes that result from the application of different remineralization agents by Raman analysis. The aim of this study was to determine the PO 4 À3 changes of enamel surfaces by using Raman analysis, as a result of applying three different remineralization agents containing Ca-PO 4 À3 (CPP-ACP + F, TCP + F, ACP + F) in in vitro conditions and to compare the remineralization capacity of these agents.…”
Section: à3mentioning
confidence: 99%